IMPORTANCE AND PERFORMANCE OF PUBLIC TRANSPORTATION SERVICES BASED ON WOMEN'S PERCEPTIONS - Atik Wahyuni; Sri Wiwoho Mudjanarko; Emil Adly (Universitas Jember, 2020)
Current transportation planning policies have not taken into account the needs of women, especially public transport services have not been able to provide a sense of security and comfort and convenience (Agustina, 2007). Preliminary findings indicate that failure to produce transport policies and provisions that meet the needs of women has worsened socioeconomic conditions (ILO, 2011). Women must become movers to make changes to get women's rights in public space including in public transportation (Harrison J, 2012). For this reason, it is necessary to know the performance indicators of public transport services that need to be improved and to know the current performance of public transport services according to women's perceptions. Using the IPA method, conclusions based on the perception of women using sub variable public transport that require priority to improve services are lighting at stops (X1.2) and also in transportation (X1.4), vehicle identity (X1.7), driver identification (X1.8), vehicle worthiness (X2.3), standing passenger handling facilities (X2.7), transport capacity (X3.7), the comfort of lighting at the stop (X3.1) and inside transportation (X3. 6), temperature control facilities in transportation (X3.8), accessibility (X4.1), ease of movement (X5.1), integration between projects (X5.2), tariff (X5.3), waiting time (X6 .1), travel speed (X6.2), stop time at stop (X6.3), stop / lane information to be traversed (X6.4), arrival schedule (X6.5) and departure (X6.6), (2) The average level of satisfaction of women users of public transport is 2.25 and the average desirability of priority handling is 4.33 from a scale of 5. The order of variables that must be increased is (1) (X6), (2) Security (X1), and Comfort (X3), (3) Affordability (X5), (4) Safety (X2) and (5) Equality (X4). Kebijakan perencanaan transportasi saat ini belum mempertimbangkan kebutuhan kaum perempuan, terutama pelayanan angkutan umum belum mampu memberikan rasa aman dan nyaman dan kemudahan (Agustina, 2007). Temuan awalmenunjukkan bahwa kegagalan untuk menghasilkan kebijakan transportasi dan ketentuan yang memenuhikebutuhan perempuan telah memperburuk kondisi sosial ekonomi (ILO, 2011). Perempuan harus menjadipenggerak untuk melakukan perubahan untuk mendapatkan hak perempuan di ruang publik termasuk didalam transportasi umum( Harrison J, 2012). Untuk itu perlu mengetahui indikator kinerja pelayanan angkutan umum yang perlu ditingkatkan dan mengetahui kinerja pelayanan angkutan umum yang ada saat ini menurut persepsi perempuan. Dengan menggunan metode IPA diperoleh kesimpulan berdasarkan persepsi perempuan pengguna angkutan umum subvariabel yang memerlukan prioritas peningkatan pelayanan adalah lampu penerangan di halte (X1.2) dan juga di dalam angkutan (X1.4), identitas kendaraan (X1.7), tanda pengenal pengemudi (X1.8), kelaikan kendaraan (X2.3), fasilitas pegangan untuk penumpang berdiri (X2.7), kapasitas angkut (X3.7), kenyamanan lampu penerangan di halte (X3.1) dan di dalam angkutan(X3.6), fasilitas pengatur suhu di dalam angkutan (X3.8), aksesibilitas (X4.1), kemudahan perpindahan (X5.1), integrasi antar proyek (X5.2), tarif (X5.3), waktu tunggu (X6.1), kecepatan perjalanan (X6.2), waktu berhenti di halte (X6.3), informasi halte/jalur yang akan dilewati(X6.4), ketepatan jadwal kedatangan(X6.5) dan keberangkatan (X6.6), (2) Rata-ratatingkat kepuasan perempuan pengguna angkutan umum 2,25 dan rata-rata keinginan prioritas penanganan 4,33 dari skala 5. Urutanvariabel yang harus ditingkat adalah (1) Keteraturan (X6), (2) Keamanan (X1) dan Kenyamanan (X3), (3) Keterjangkaun (X5), (4) Keselamatan (X2) dan (5) Kesetaraan (X4).